Challenging a dogma: co-mutations exist in MAPK pathway genes in colorectal cancer. - Grellety, Thomas; Gros, Audrey; Pedeutour, Florence; Merlio, Jean-Philippe; Duranton-Tanneur, Valerie; Italiano, Antoine; Soubeyran, Isabelle (Virchows Archiv: European Journal of Pathology, 2016)
Sequencing of genes encoding mitogen-activated protein kinase (MAPK) pathway proteins in colorectal cancer (CRC) has established as dogma that of the genes in a pathway only a single one is ever mutated. We searched for cases with a mutation in more than one MAPK pathway gene (co-mutations). Tumor tissue samples of all patients presenting with CRC, and referred between 01/01/2008 and 01/06/2015 to three French cancer centers for determination of mutation status of RAS/RAF+/-PIK3CA, were retrospectively screened for co-mutations using Sanger sequencing or next-generation sequencing. We found that of 1791 colorectal patients with mutations in the MAPK pathway, 20 had a co-mutation, 8 of KRAS/NRAS, and some even with a third mutation. More than half of the mutations were in codons 12 and 13. We also found 3 cases with a co-mutation of NRAS/BRAF and 9 with a co-mutation of KRAS/BRAF. In 2 patients with a co-mutation of KRAS/NRAS, the co-mutation existed in the primary as well as in a metastasis, which suggests that co-mutations occur early during carcinogenesis and are maintained when a tumor disseminates. We conclude that co-mutations exist in the MAPK genes but with low frequency and as yet with unknown outcome implications.